ENTREPRENEURSHIP OF MEMORY IN PUBLIC SPACE AND SOCIAL COMMUNICATION: A POSTCOLONIAL APPROACH IN TIME OF WAR - Viktoriia Kovpak; Nataliia Lebid; Viktor Burenkov (Baltic Journal of Economic Studies)
In the context of the experience economy, memory entrepreneurship has emerged as a significant phenomenon during wartime. It has a robust set of tools at its disposal, capable of producing, demonstrating, popularising, reinterpreting and reproducing historical representations or alternative narratives through public cultural platforms, such as private and public museums, as well as the business industry. Citizens, as objects of this entrepreneurial activity, play a crucial role in supporting the mechanism of personal identification with these narratives. They become an integral part of the public reproduction of memory and group identity. Therefore, the subject of research is commercial representations of historical narratives in case studies of memory entrepreneurship that iclude heritage restaurants ("restaurants of historical heritage"). The purpose of the research is to analyse cases of constructive and destructive use of organisational imprinting in the economy as a strategic practice of memory politics, using the example of "heritage restaurants". The research methodology is based on a combination of systematic, value and postcolonial approaches, discourse analysis, which contribute to the disclosure of principles and strategies of Ukrainian cases of memory entrepreneurship, their correlation with the peculiarities of civil society demands for national identity proposals in the conditions of war. The synchronous method (focusing on the conditions of a full-scale Russia's invasion of Ukraine) is also used with the monitoring programme of the information space Brand24 for the indicators of brand representation in the media. The article emphasizes that, according to B. Joseph Pine II and D. G. Gilmore, in order to create coherent, powerful impressions, it is necessary to follow five basic principles: choose the theme of the impressions, harmonize them with positive signals, eliminate negative signals, use different ways of fixing memories, and engage all five senses. The effectiveness of the use of such principles is analysed from a postcolonial perspective using the examples of regional restaurant business cases that construct the politics of memory by representing commercial historical narratives. In the discourse of the creative industries and the creative economy, it is appropriate to consider the model of the experience economy, which operates creatively in the context of the "memory of emotional experience" and strategically intersects with the discourse of the politics of memory. This, in turn, can take the form of the construction of historical memory and become a practice of intervention in the field of historiography, marking the territory and the mental space with colonial symbols, as demonstrated by Russia after the collapse of the USSR, appealing to nostalgia for the Soviet past and constructing the politics of "fraternal nations" in entrepreneurial activity. An important part of the article is the description of interpretive approaches in the discourse of postcolonial studies in the interpretation of the concept of "memory entrepreneurship", which has its origin in the discourse of desegregation of the past in the United States and South Africa. Therefore, the conclusion of the scientific research includes theses on conceptual value approaches in the politics of memory that underlie the constructive or destructive use of organisational imprinting (the mechanism of persistent memorisation and subsequent remembering as a consequence of the systemic mechanism of broadcasting national and cultural memories and the construction of national identity) in entrepreneurial activity as a strategic practice of the impression economy model.